Research on the Application of Multimedia in the Teaching of Electrical Machinery - Nan, Xie; Dantes, Gede Rasben; Divayana, Dewa Gede Hendra; Santosa, Hery (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
This study aims to explore the specific application modes, practical effects, and existing challenges of multimedia technology in the teaching of Electrical Machinery, a core course in engineering disciplines. Guided by the Dual Coding Theory and Cognitive Load Theory, an analytical framework was constructed, and a sequential explanatory mixed-methods research design was adopted. A controlled experiment was conducted with two classes (n=92) of electrical engineering majors from a university, and both quantitative and qualitative data were collected through questionnaires, in-depth interviews, and classroom observations. The key findings are as follows: (1) The systematic application of multimedia resources such as 3D animations and simulation software significantly improved students’ performance in understanding complex electromagnetic concepts and cognizing spatial structures (p < .01); (2) Multimedia effectively stimulated students’ learning interest by creating contextualized scenarios, but improper design could increase extraneous cognitive load; (3) The in-depth integration of multimedia with traditional blackboard writing and physical models is the key to achieving effective teaching outcomes. Based on these findings, a "complementary integration" teaching framework was established, which provides theoretical references and practical pathways for optimizing the instructional design of engineering professional courses.